Behavioral Measurement of Trust in Automation: The Trust Fall. (September 2016) - Miller, David; Johns, Mishel; Mok, Brian; Gowda, Nikhil; Sirkin, David; Lee, Key; Ju, Wendy
Stating that one trusts a system is markedly different from demonstrating that trust. To investigate trust in automation, we introduce the trust fall: a two-stage behavioral test of trust. In the trust fall paradigm, first the one learns the capabilities of the system, and in the second phase, the 'fall, ' one's choices demonstrate trust or distrust. Our first studies using this method suggest the value of measuring behaviors that demonstrate trust, compared with self-reports of one's trust. Designing interfaces that encourage appropriate trust in automation will be critical for the safe and successful deployment of partially automated vehicles, and this will rely on a solid understanding of whether these interfaces actually inspire trust and encourage supervision.